Phosphorylated retinoblastoma is a biomarker of overall disease control and better progression-free survival of recurrent epithelial ovarian cancer patients treated with second-line topoisomerase inhibitor CPT-11 chemotherapy - Jiang, Kui; Gao, Guangyan; Yao, Lulu (Translational Cancer Research, 2018)
Background: To determine the association of phosphorylated retinoblastoma (p-RB) with the clinical outcome of recurrent epithelial ovarian cancer (EOC) patients after CPT-11 chemotherapy. Methods: We enrolled 27 recurrent EOC patients who had failed first-line chemotherapy and underwent second-line and above CPT-11 chemotherapy from January 2002 to September 2016 in our hospital. The complete medical records of the patients were retrospectively reviewed. The phosphorylation of RB at Ser780 (p-RB) in surgical tumors and 27 normal ovarian tissues was assessed by immunohistochemistry. Results: The positive rate of p-RB expression in EOC tissues was significantly higher than that in normal ovarian tissues (62.96% vs. 22.22%, P0.05). In addition, p-RB expression was significantly associated with disease control rates of CPT-11 chemotherapy (P